Blind study site assessment of shear-wave velocity at Kumamoto City, Japan, using direct-fitting SPAC methods - Michael Asten; Aysegul Askan; Shaghayegh Karimzadeh (Earth, Planets and Space, 2023)
Abstract The study used data acquired by the ESG6 Blind Prediction Step BP1 Working Group for purposes of facilitating a comparison of interpretation methods for obtaining shear-wave velocity profiles (Vs) from array observations of microtremor (passive seismic) noise. This work uses the direct-fitting MMSPAC method and the krSPAC method on passive seismic data supplied from four seven-station nested triangular arrays with apertures ranging from 1 to 962 m, located within Kumamoto City, Japan. The data allow a useful frequency range of 38 Hz down to 0.3 Hz, giving depth sensitivities from 2 m to > 1000 m. Results are presented as a seven-layer model which has time-averaged shear wave velocities for top 30 m and 300 m of V s30 = 189 m/s and V s300 = 584 m/s, respectively. HVSR spectra show two significant peaks at 1.2 and 0.35 Hz which are indicative of major Vs contrasts at depths 26 m and 750 m. The MMSPAC method (and its krSPAC variant) also proved viable on one asymmetric array where four of the seven stations were corrupted by incoherent low-frequency noise. Indications of a lateral variation in Vs could be detected due to the non-concentric geometry of the four arrays, and also from variations in HVSR spectra at stations of the largest array. Further analysis in step 4 of the blind trials, making use of geological data and a Preferred model supplied to participants, showed apparent discrepancies between the Preferred and our BP1 model for the upper 40 m where a supplied PS log appears to be inconsistent with geological data and the blind BP1 model. At low frequencies 0.5–2.5 Hz dispersion data and the BP1 model suggest that use of the Rayleigh effective mode is superior to use of the fundamental mode in deducing the Vs model at depths below 100 m. The method of direct fitting of model and observed SPAC spectra used in MMSPAC also enabled the use of a bandwidth 0.5–38 Hz for interpretation, which is a wider bandwidth than that achieved by other participants for use of passive seismic data alone. Graphical Abstract